Integrated care in German mental health services as benefit for relatives: a qualitative study - Valentini, Jan; Ruppert, Daniel; Magez, Julia; Götz, Katja (BMC psychiatry, 2016)
As mental health services undergo the process of deinstitutionalization, this is resulting in a higher burden of care for relatives. Evidence suggests that interventions for carers have a beneficial impact on their psychological health. A reduction of responsibility for relatives is linked with a significantly improved outcome for the severely mentally ill. The aim of the study was to explore the relatives’ experiences with severely mentally ill patients in different integrated care service providers.